2003
DOI: 10.1007/s00420-003-0436-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breath, blood and urine concentrations in the biomonitoring of environmental exposure to 1,3-butadiene, 2,5-dimethylfuran, and benzene

Abstract: 1,3-Butadiene and benzene, as ubiquitous pollutants, are detectable and quantifiable in human alveolar air, blood and urine. 2,5-Dimethylfuran, which is not a usual environmental pollutant, is almost always detectable in biological media, but only in smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 23 publications
(27 reference statements)
5
31
0
Order By: Relevance
“…and Perbellini et al (2003) reported median blood 2,5-dimethylfuran levels of 0.13 µg/L in smokers which were similar values to the 95 th percentile in participants of NHANES 2003-2004 reflecting the U.S. population mix of nonsmokers and smokers. Levels of 2,5-dimethylfuran in blood increase generally with the number of cigarettes smoked per day .…”
Section: Biomonitoring Informationsupporting
confidence: 56%
“…and Perbellini et al (2003) reported median blood 2,5-dimethylfuran levels of 0.13 µg/L in smokers which were similar values to the 95 th percentile in participants of NHANES 2003-2004 reflecting the U.S. population mix of nonsmokers and smokers. Levels of 2,5-dimethylfuran in blood increase generally with the number of cigarettes smoked per day .…”
Section: Biomonitoring Informationsupporting
confidence: 56%
“…Benzene represents a compound typically occurring in cigarette smoke and being stored in different body compartments [4,[23][24][25]. In this study, all patients were ex-smokers.…”
Section: Lung Cancer S Kischkel Et Almentioning
confidence: 99%
“…The trace-level analytical techniques used for toxicology and the high-tech medical, clinical, and environmental applications are rarely what come to mind first. However, breath has now joined blood and urine as an important diagnostic biofluid for all kinds of analyses for chemical exposures, biological response, metabolism kinetics, health state assessment, multiple time point assessments, and toxicological effects monitoring (Perbellini et al 2003;Wallace et al 1987a, b, c). In fact, breath biomarkers have demonstrated particular advantages over blood and urine in that breath sampling provides an essentially inexhaustible supply, does not require medical personnel or privacy, is noninvasive, and does not produce potentially infectious waste such as needles, bandages, and glassware (Wallace et al 1986;Amann and Smith 2005;Pleil 2008).…”
Section: Introductionmentioning
confidence: 99%